The use and significance of vaccination cards - Abram L. Wagner (Taylor & Francis Group, 2019)
Vaccination cards are useful health records that contain information about vaccination dates and dosage. This information is helpful for parents, vaccination providers, and public health researchers. However, as they currently are structured, many vaccination cards are very difficult to read by non-experts, like parents, and even by health-care providers. Many families also lose these vaccination cards; among the top 10 countries with the most unvaccinated children, the proportion of families who were able to find their vaccination cards and give them to researchers was low, ranging from 20.7% in the Democratic Republic of the Congo to 69.2% in South Africa. Moreover, some families report that not having a vaccination card during a vaccination visit resulted in them being unable to obtain a vaccine (8% in one study in Ethiopia and 16% in one study in Bangladesh). This commentary provides recommendations about how vaccination cards should be used by parents, health-care providers, and researchers, and comments on their continued relevance in an era with increased use of electronic registries.